Microeconomics study guide - Copeland, Doug; Besanko, David 1955-.; Braeutigam, Ronald R. (Ronald Ray).; Gibbs, Michael; Besanko, David 1955- .; Braeutigam, Ronald R. (Ronald Ray). ([Hoboken, N.J.] John Wiley & Sons, 2011)
This study guide accompanies Microeconomics, 4th edition by David Besanko and Ron Braeutigam.
Acquired through Health Policy Development Program (HPDP) research grant.
Keywords: Microeconomics; Microeconomics -- Study guides; Microeconomics -- Examinations -- Study guides